Educação musical inclusiva e formação de professores: contribuições da Pedagogia Histórico-Crítica (Orfeu, 2023)
This article aims to offer contributions to the discussion on the training of teachers in Music from the perspective of Inclusive Education, with Historical-Critical Pedagogy as theoretical support. It situates the problematic of education in a socio-historical context, initially presenting some conceptions that are relevant to understand the theoretical basis adopted, which are based on historical-dialectical materialism. It discusses the academic-professional training in Music in an expanded way, locating some fields of dispute, such as the imbalances between theory and practice and the Conservatory Model and Active Methods. By dealing specifically with the perspective of Inclusive Education, it locates the Medical Model and the Social Model of disability as parameters to understand the socio-historical conditioning factors that have repercussions on society and Education. It brings some suggestions for teacher training, such as the qualification of internships, the insertion of disciplines and other equally relevant subjects.
Keywords: music teacher training; inclusive Music Education; historical-critical Pedagogy